HDAC4 Knockdown Alleviates Denervation-Induced Muscle Atrophy by Inhibiting Myogenin-Dependent Atrogene Activation - Ma, Wenjing; Cai, Yong; Shen, Yuntian; Chen, Xin; Zhang, Lilei; Ji, Yanan; Chen, Zehao; Zhu, Jianwei; Yang, Xiaoming; Sun, Hualin (Frontiers in Cellular Neuroscience, 2021)
Denervation can activate the catabolic pathway in skeletal muscle and lead to progressive skeletal muscle atrophy. At present, there is no effective treatment for muscle atrophy. Histone deacetylase 4 (HDAC4) has recently been found to be closely related to muscle atrophy, but the underlying mechanism of HDAC4 in denervation-induced muscle atrophy have not been described clearly yet. In this study, we found that the expression of HDAC4 increased significantly in denervated skeletal muscle. HDAC4 inhibition can effectively delay denervation-induced muscle atrophy, reduce the expression of muscle specific E3 ubiquitin ligase (MuRF1 and MAFbx) and autophagy related proteins (Atg7, LC3B, PINK1 and BNIP3), inhibit the transformation of type I fibers to type II fibers, and enhance the expression of SIRT1 and PGC-1 α. Transcriptome sequencing and bioinformatics analysis was performed and suggested that HDAC4 may be involved in denervation-induced muscle atrophy by regulating response to denervation involved in regulation of muscle adaptation, cell division, cell cycle, apoptotic process, skeletal muscle atrophy, and cell differentiation. STRING analysis showed that HDAC4 may be involved in the process of muscle atrophy by directly regulating myogenin (MYOG), cell cycle inhibitor p21 (CDKN1A) and salt induced kinase 1 (SIK1). MYOG was significantly increased in denervated skeletal muscle, and MYOG inhibition could significantly alleviate denervation-induced muscle atrophy, accompanied by the decreased MuRF1 and MuRF1. MYOG overexpression could reduce the protective effect of HDAC4 inhibition on denervation-induced muscle atrophy, as evidenced by the decreased muscle mass and cross-sectional area of muscle fibers, and the increased mitophagy. Taken together, HDAC4 inhibition can delay denervation-induced muscle atrophy by reducing MYOG expression, and HDAC4 is also directly related to CDKN1A and SIK1 in skeletal muscle, which suggests that HDAC4 inhibitors may be a potential drug for the treatment of neurogenic muscle atrophy. These results not only enrich the molecular regulation mechanism of denervation-induced muscle atrophy, but also provide experimental basis for HDAC4-MYOG axis as a new target for the prevention and treatment of muscular atrophy.